Integrated Single Item Lot-Sizing and Quality Inspection Planning. Issue 12 (2016) - Bettayeb, B.; Brahimi, N.; Lemoine, D.
Abstract: This paper proposes an integrated model for Single Item Dynamic Lot-Sizing (SIDLS) problem and Quality Inspection Planning (QIP). The objective is to provide a model of production planning that takes into account a targeted level of outgoing quality (AQL: Acceptable Quality Level) when the manufacturing system inherently generates a proportion of defectives that increases significantly when the system switches from the in-control state to the out-of-control state. The Average Outgoing Quality (AOQ) of each period of time of the planning horizon is bounded as a function of the inspection capacity. The effects of integrating quality inspection planning are analyzed and discussed through several experiments representing different quality control system's parameters, i.e. inspection capacity, inspection cost and AQL.